Diagnostic accuracy of bronchodilator responsiveness in wheezy children. Issue 1 (23rd December 2004) - Dundas, I; Chan, E Y; Bridge, P D; McKenzie, S A
Abstract : Background: The aim of this study was to evaluate the diagnostic accuracy of bronchodilator responsiveness for asthma in 5–10 year old children. Methods: Spirometric measurements were made in 142 children (58 wheezers) before and after 400 μg inhaled salbutamol. Results: On a receiver operating characteristic curve, a 9% increase in predicted forced expiratory volume in 1 second was the cut off point that provided an acceptable balance of sensitivity and specificity for previous wheeze. This figure was 50% (95% CI 38 to 62) sensitive and 86% (95% CI 78 to 92) specific for detecting previous wheeze and multiplied the initial odds in favour of wheeze by a factor of 3.6 (95% CI 2.0 to 6.3). Discussion: With an estimated pretest probability of wheeze of 10% in the community and 50% in a specialist clinic, the positive predictive values are 29% and 78%, respectively, for a 9% change. The value of bronchodilator responsiveness testing depends on the prevalence of wheeze in the population in which it is to be used.